Improving argumentative writing: Effects of a blended learning approach and gamification - Lam, Yau Wai; Hew, Khe Foon; Chiu, Kin Fung (Language learning & technology, 2018)
This study investigated the effectiveness of a blended learning approach—involving the thesis, analysis, and synthesis key (TASK) procedural strategy; online Edmodo discussions; online message labels; and writing models—on student argumentative writing in a Hong Kong secondary school. It also examined whether the application of digital game mechanics increased student online contribution and writing performance. Three classes of Secondary 4 students (16- to 17-year-olds) participated in the 7-week study. The first experimental group (n = 22) utilized the blended learning + gamification approach. The second experimental group (n = 30) utilized only the blended learning approach. In the control group (n = 20), a teacher-led direct-instruction approach on the components of argumentation was employed. Data sources included students’ pre- and post-test written essays, students’ online Edmodo postings, and student and teacher interviews. We found a significant improvement in students’ writing using the blended learning approach. On-topic online contributions were significantly higher when gamification was adopted. Student and teacher opinions on the blended learning approach were also examined.